Driving Foreign Tourist to Bandung: The Traveloka Travel Friends Project Design - Mochamad Dival Harsyauqi; Kurnia Khafidatur Rafiah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The goal of the Traveloka Travel Friends Bandung campaign is to increase demand for Traveloka's lodgings through the use of social media channels like TikTok. However, the content that the Traveloka Travel Friends Bandung group shares via TikTok's For You Page (FYP) function is not perfect in terms of reaching international visitors. To assess where things are now, we use the SOSTAC method, which stands for